2018
DOI: 10.1016/j.jcf.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Young patients with cystic fibrosis demonstrate subtle alterations of the cardiovascular system

Abstract: Our study suggests that already at a very young age, children with cystic fibrosis show an increased arterial stiffness and some signs of diminished both right and left ventricular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 30 publications
(43 reference statements)
0
34
0
Order By: Relevance
“…While ventricular function appeared to be normal in TTE, both techniques gave results confirming subclinical ventricular dysfunction. 5,8,10,26 Pulmonary artery systolic pressure as measured based on the tricuspid regurgitation (TR) jet was higher in the CF patients group than in controls. an abnormal interventricular septal motion may also affect LV function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While ventricular function appeared to be normal in TTE, both techniques gave results confirming subclinical ventricular dysfunction. 5,8,10,26 Pulmonary artery systolic pressure as measured based on the tricuspid regurgitation (TR) jet was higher in the CF patients group than in controls. an abnormal interventricular septal motion may also affect LV function.…”
Section: Discussionmentioning
confidence: 99%
“…They did not find any differences in total global, mid, and apical strain values. 26 This suggested that total cardiac involvement might be related to the duration of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…While the effects of severe lung disease on cardiovascular health in CF are well known, cardiovascular health in CF children has had less attention. A study of 33 children with CF, aged 3 to 12 years, and 33 age‐matched controls were selected from a population‐based cohort study . Measures of pulmonary function, arterial stiffness, and echocardiographic measures were compared.…”
Section: Multisystem Effects Of Cystic Fibrosismentioning
confidence: 99%
“…A study of 33 children with CF, aged 3 to 12 years, and 33 age-matched controls were selected from a population-based cohort study. 39 Thus, while specific patient-and catheter-related risk factors were identified, attention to center practices including insertion, maintenance and anticoagulation may be a target for reducing complications of the more commonly used PICCs.…”
Section: Cardiovascular Systemmentioning
confidence: 99%
See 1 more Smart Citation